MANDARIN, PUTONGHUA AND CHINESE DIALECTS - Nurmatov Yorqin Irkinovich (Bright Mind Publishing, 2025)
Despite the growth in popularity of Chinese medicine over recent decades, the westward transmission of Chinese medical knowledge continues to be hampered by a number of problems, including a low level of linguistic access to primary Chinese sources, a low level of translation, and a lack of a standardized English terminology.
Keywords: Medical concepts, tоu (t´ou) (頭), lin ba (l´ın b¯a) (淋巴), ideograms, nong siong (n´ong xi¯ong) (膿胸), fu shui (f`u shuˇı) (腹水), nei (nèi) (内) and vey (wèi) (外), Chinese medical concepts, English and Chinese terminology and standardization.